Coefficient Bounds for Some Families of Starlike and Convex Functions of Reciprocal Order - Muhammad Arif; Maslina Darus; Mohsan Raza; Qaiser Khan (The Scientific World Journal)
The aim of the present paper is to investigate coefficient estimates, Fekete-Szegő inequality, and upper bound of third Hankel determinant for some families of starlike and convex functions of reciprocal order.